Desenvolvimento de blendas poliméricas policarbonato/ poli (Tereftalato de Butileno) (PC/PBT) compatibilizadas e nanoestruturadas - Laurindo, Vanessa (Universidade Federal de São Carlos, 2012)
The evaluation of addition of a random copolymer as compatibilizing and his effect in obtaining nanostructured morphology in blends composed by PC as matrix and PBT as dispersed phase, were investigated. The copolymercompatibilizer was produced by reactive mixture, in a torque rheometer, of the components of blend PC/PBT (50/50%wt) in the presence of different concentrations of the catalyst TnBT (1000 and 2000 ppm) and different mixing times (10 and 30 minutes). The characterization of thermal and chemicals properties by DSC, FTIR and 1HNMR showed evidences of the occurrence of transesterification reactions between the blends components for all systems studied. However, formation of the random copolymer was confirmed only for the system with addition of 2000 ppm of the catalyst, subjected to different mixing times. To minimize the effects of degradation reactions in the random copolymer formed, was selected use as compatibilizer to obtain nanostructured blends, the copolymer obtained after 10 minutes of mixing. To evaluating effect of the copolymer-compatibilizer in obtain a nanostructured morphology, were prepared blends PC/PBT (95/5%wt) with addition of 0, 1, 3 and 5% wt of copolymer and by the thermal analysis by DSC and DMTA was observed the existence of a partial miscibility, restricted to the amorphous phase, between the components of the blends PC/PBT studied. Morphological analysis by TEM revealed to obtain a dispersed phase nanostructured for the blend with addition of 3%wt of compatibilizing. The effect of random copolymer as compatibilizing agent for the blends studied was also demonstrated by characterization of the mechanical properties of tensile and impact.
Development of polycarbonate/ poly (terephthalate) (pc/pbt) polymer blends compatibilized and nanostructured
Keywords: Blendas poliméricas; Nanoblendas; Transesterificação; Compatibilização reativa; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA